Pendampingan Pola Asuh Orang Tua terhadap Anak Usia Sekolah Dasar Di Kelurahan Blabak Kecamatan Pesantren Kota Kediri - Putri, Kharisma Eka; Saidah, Karimatus; Fahmi Imron, Ilmawati; Primasatya, Nurita; Damariswara, Rian; Aditia Wiguna , Frans; Nur Wenda, Dhian Dwi; Andri Aka, Kukuh; Abidah, Bintan (Universitas Nusantara PGRI Kediri, 2023)
The purpose of this service is to provide assistance to the community of Blabak Village, Pesantren District, Kediri City about the importance of Parenting Education (Parenting) for parents of elementary school-age children. This activity was attended by 23 mothers of posyandu and PKK cadres who have elementary school-age children and was carried out on March 8, 2023. The method used in this service activity consists of a planning stage, namely observing the needs of the community in Blabak village so that problems related to parenting are obtained, an implementation stage with the delivery of material and questions and answers about parenting and an evaluation stage regarding filling out questionnaires by mentoring participants regarding parenting. Through this activity, it was found that the community who participated in the activity gave a positive response, and even hoped that the activity could be carried out on an ongoing basis so that more knowledge could be obtained related to parenting patterns of parents of elementary school-age children, so that with the right parenting patterns can make children become good characters.